THE EFFECT OF CLIMATE ON RADIAL GROWTH OF SCOTS PINE (Pinus sylvestris L.) IN A COASTAL MIXED STAND IN KAPISUYU, BARTIN, TURKEY - Barış Özel, Halil; Yaman, Barbaros; Varol, Tuğrul (Indonesian Journal of Forestry Research, 2021)
Scots pine is geographically the most widespread pine species in the world, and it shows different growth responses to climate and environmental factors in diverse ecological sites. We studied both the stand dynamics and climate-growth relationships of scots pine in isolated coastal stand (recently found) in the Western Black Sea Region of Turkey. The homogeneity index of this stand has varied between 1.92–3.56. In growth-ring analyses, after cross-dating of individual chronologies, COFECHA and ARSTAN software were used respectively for chronology quality control and standardization (detrend). In this way, a 58-year-long chronology (1959-2016) of scots pine was constructed. In addition, DENDROCLIM software was used for investigating scots pine’s radial growth-climate relationships. Mean sensitivity changed from 0.163 to 0.331, with a mean of 0.183. Mean correlation among trees and signal to noise ratio were 0.389 and 7.012 respectively. In terms of the effect of precipitation on the radial growth of scots pine in this site, the correlation coefficients were 0.43 (p<0.05) for December of the previous year and 0.41 (p<0.05) for July of the current year. For all the other months, precipitation had a non-significant effect. As for the maximum and mean air temperature, the correlation coefficients were 0.36 (p<0.05) and 0.40 (p<0.05) for February, and 0.40 (p<0.05) and 0.42 (p<0.05) for March, respectively. However, on the radial growth, while the maximum temperature in August had a negative effect (r= -0.26; p<0.05), minimum temperatures in February, March and July had a positive effect (r= 0.39, 0.40 and 0.34 respectively; p<0.05).